2008
DOI: 10.1530/eje-07-0709
|View full text |Cite
|
Sign up to set email alerts
|

Increased basal and pulsatile secretion of FSH and LH in young men with 47,XXY or 46,XX karyotypes.

Abstract: Objective: The regulation of normal sexual maturation and reproductive function is dependent on a precise hormonal regulation at hypothalamic, pituitary, and gonadal levels. The aim of this study was to investigate the neuroendocrine integrity of the pituitary-gonadal axis in patients with primary testicular failure due to supernumerary X chromosomes. Design: Cross-sectional study. Methods: In this study, 7 untreated patients with primary gonadal insufficiency due to SRY-positive 46,XX (nZ4) and 46,XXY karyoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…The same results have been reported by Ottesen et al (2010) and Aksglaede et al (2008). The same results have been reported by Ottesen et al (2010) and Aksglaede et al (2008).…”
Section: Discussionsupporting
confidence: 89%
“…The same results have been reported by Ottesen et al (2010) and Aksglaede et al (2008). The same results have been reported by Ottesen et al (2010) and Aksglaede et al (2008).…”
Section: Discussionsupporting
confidence: 89%
“…A study by Aksglaede describing 9 boys, ages 9.2-20 years, also reported 1 boy with an extremely high FSH and an immeasurably low inhibin B. 18 This constellation can be seen in Sertoli-cell-only syndrome, which has been reported in adults with XYY, 11,45-47 and is associated with decreased fertility. Gonadal histology in a study of XYY fetuses showed fewer spermatogonia than in XY controls.…”
Section: Discussionmentioning
confidence: 93%
“…1,6,18 There are reports of genitourinary anomalies, including microphallus, hypoplastic scrotum, cryptorchidism, and hypospadias in XYY. 11,19 …”
mentioning
confidence: 99%
“…Then, germ cells fail to progress through meiosis and undergo apoptosis at puberty leading to reduced testis volume and azoospermia. Testosterone secretion is most frequently subnormal or clearly low, and gonadotropins are elevated in the adult (Vorona et al, 2007;Aksglaede et al, 2008).…”
Section: Foetal-onset Hypogonadism Foetal-onset Primary Hypogonadismmentioning
confidence: 99%